Effects of hypothermia on blood endogenous endotoxin levels during cardiopulmonary bypass - (:unkn) unknown (Blackwell Publishing Inc., 1997)
Endotoxin activates white blood cells and complement and produces a spectrum of clinical syndromes ranging from fever to septic shock. Although production of endogenous endotoxemia during cardiopulmonary bypass (CPB) has recently been reported, the role of hypothermia on endotoxemia is not clear. In this study, we evaluated the effects of moderate (24-28°C) and mild (32- 34°C) hypothermia on blood endotoxin levels. The study population consisted of 20 patients who underwent coronary artery bypass grafting (CABG) with CPB. Moderate systemic hypothermia was applied during aortic cross-clamping in ten patients (group 1) and mild hypothermia in the remaining ten patients (group 2). The mean rectal temperatures were 26.8 ± 1.2°C in group 1 and 33.8 ± 0.8°C in group 2. The blood samples for endotoxin level measurements were obtained before CPB, during aortic cross-clamping, immediately after the release of the cross-clamp, 20 minutes after the release of the cross-clamp, after CPB, and 2 hours postoperatively. There were no endotoxins in any of the samples before CPB, but it was detected after CPB in both groups. The endotoxin levels were significantly higher in group I than in group 2. The present study suggests that when hypothermia is the technique of choice, the deleterious effects of endotoxemia on patients with comorbidity must be considered.